The Global Refunding System and Climate Change - Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
We propose a global refunding scheme as a new international approach to addressing climate change. A global refunding system allows each country to set its carbon emission tax, while aggregate tax revenues are partially refunded to member countries in proportion to the relative emissions reduction they achieve within a period. Nationally determined environmental policies and global refunding create increasing incentives to reduce emissions and may achieve e±ciency and equity objectives of global climate policy.
Keywords: 330; Klimawandel; Internationale Umweltpolitik; Emissionshandel; Welt